A Study on The Application of Convoluted PTFE For Arterial Implantation: Mechanical Testing and Properties. (May 2020) - Tariq, Mohammed Gulfaraz; Youseffi, Mansour; Jamil, Muhammad Mahadi bin Abdul; Rahman, Nur Adilah Abd; Khaghani, Seyed Ali; Sefat, Farshid
Abstract: Polytetrafluoroethylene (PTFE) is a thermoplastic polymeric material with various applications including aerospace, automotive, biomedical and electrical. PTFE surface is smooth, wear resistant, non-sticky and slippery in nature. Combined with such useful properties, the material conveys various other features such as temperature resistance up to 260°C, exceptional chemical stability, corrosion resistance, good fatigue strength and sterilisable. This work involved mechanical testing of convoluted PTFE tubes with different thicknesses, diameters and lengths. This included the following tests: volumetric expansion, tensile and elongation, rolling u wear and burst tests by applying real industrial pressures. The mechanical testing showed promising results for the convoluted PTFE tubes which could undergo extreme elongation due to the elastic nature. The % volumetric expansion exceeded the expected values (on average, 3-5% higher than the expected values). The results for the rolling u wear, burst and tensile tests also showed good properties. Based on its mechanical properties, convoluted PTFE seemed to be an appropriate material for replacing damaged/diseased arteries.